Hepatic transcriptome and proteome analyses provide new insights into the regulator mechanism of dietary avicularin in diabetic mice. (November 2019) - Zhu, Xiaoai; Qiu, Zhirou; Ouyang, Wen; Miao, Jianyin; Xiong, Ping; Mao, Duobin; Feng, Konglong; Li, Minxiong; Luo, Minna; Xiao, Hang; Cao, Yong
Abstract: Many dietary flavonoids existing as glycosides in fruits and vegetables are considered bioactive food components with various potential health benefits. Type 2 diabetes mellitus (T2DM) is a complex and polygenic disease with increasing global prevalence and economic burden. In this study, the hypoglycemic effect of avicularin (quercetin-3-O-α-arabinofuranoside), a flavonoid glycoside commonly found in natural plants and fruits, was determined in a high fat diet/streptozotocin induced type 2 diabetes mouse model. Our results demonstrated that dietary avicularin treatment reduced levels of fasting blood glucose, serum TG and LDL-C, liver AST and ALT, and increased hepatic glycogen in T2DM mice. Furthermore, we used RNA-Seq and iTRAQ to compare the gene and protein expression in the livers of the normal control mice (NC), diabetic control mice (DC) and avicularin treated mice (DA100). The differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) were analyzed based on gene annotations and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. Integrated analysis of the RNA-Seq and iTRAQ data indicated that the fifteen DEGs/DEPs showed the same trend in mRNA and protein expression levels in comparisons of both NC vs DC and DC vs DA100. KEGG analysis revealed that four DEGs/DEPs (PKM, PEPCK, PYG, and PLA2) in the glycolysis, gluconeogenesis, and arachidonic acid pathway, and six DEPs (Ndufb4, Ndufa6, Cox5a, Cox5b, Cox6c, and ATPSβ) in the oxidative phosphorylation signaling pathway, play important roles in avicularin's hypoglycemic effect. We also found six other DEGs/DEPs related to T2DM (CA1, Serpinb6a, AK, Pcolce, Cand2, and Atp2a3), and five related to cancer (Phgdh, Tes, Papss1, Psat1, and Fam49b). We did further verify by qRT-PCR and explored the possible binding modes of avicularin with targeted proteins with molecular docking simulations. Taken together, our results demonstrated the protective effects of avicularin against diabetes and provided a global view about the system-level hypoglycemic mechanisms of avicularin by the comprehensive analysis of transcriptomic and proteomic data in T2DM mice. Graphical abstract: Unlabelled Image Highlights: The hypoglycemic effect of avicularin was determined in HFD/STZ induced T2DM mice. RNA-seq and iTRAQ were used to explored hypoglycemic mechanisms of avicularin. qRT-PCR was performed to verify the targeted genes. The possible binding modes of avicularin with targeted proteins were explored.